Ecology and parasitological analysis of horse flies (diptera: tabanidae) in antioquia, colombia (2008)
During the months of June to September 2006, collections of tabanids (Diptera:Tabanidae) and ticks were conducted in the Caucasia municipality, Antioquia,Colombia. Tabanids were caught on horses during daylight using hand nets and pots atthe ecotone zone between secondary forests and paddock habitats. Ticks were collecteddirectly from cattle by hand. The purpose of the study was to identify possible vectorsof bovine trypanosomosis, and register the diversity and abundance of tabanids inthe zone. The arthropods were brought to the laboratory for taxonomic determinationand protozooans searching in proboscis, midgut, and salivary glands of flies. Inthe case of ticks, protozoans were searched in hemolymph. One hundred and fortytabanids belonging to four genera and nine species were caught. Among the species,Lepiselaga crassipes was the most abundant (43.6%), with the highest abundancein July and a biting peak at 14:00 h. The highest diversity of tabanids was observedduring September. Three tabanids were found infected with flagellates morphologicallycompatible with Trypanosoma vivax. 315 ticks belonging to Boophilus microplusspecies were collected, all of them negative to flagellates. These results suggest T.vivax transmission by tabanids in the study area. However, the specific status ofthe parasites should be determined by molecular techniques and the transmissionmechanism should be established too by controlled studies